PENGARUH KOHESIVITAS KELOMPOK TERHADAP PRODUKTIVITAS KERJA Agen Asuransi Jiwa Bersama Cabang Sukajadi – Pekanbaru - Lastiar Sinaga; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Abstract Lastiar Sinaga. Nim 1001112042. Influence cohesivitas group against productivity work on the insurance industry branch Sukajadi - Pekanbaru supervising lecturer: Drs. Kasmiruddin M.SiCohesivitas is forces of interaction of members of a group into a motivation for each member and it is important for a group. Cohesivitas shown in the form of hospitality, among members of a group they usually happy together. Each member feel free to give opinions and " he advised. In this an assumption that cohesisvitas good will create productivity.Productivity is an impulse to try and develop themselves and have guidelines thought that the achievement of an aim must be coöperation or integrity of elements relevant as a system constituted by pengorban to maximum results.The result showed that kohesivitas influential favorably to productivity. This can be viewed from T table and it count, and value of significance variable smaller than 0.05.Keywords: cohesivitas, productivity, influence